Strike of the Sailfish : two sister submarines and the sinking of a Japanese aircraft carrier - Moore, Stephen L. (Caliber, 2023)
"A gripping true-life thriller about the first US submarine to sink a Japanese aircraft carrier-and the sub's tragic twist of fate"--